The chosen questions of the downtown cultural space revitalisation in the context of increasing Polish cities attractiveness - Pazder, Dominika (Rozwój Regionalny i Polityka Regionalna, 2013)
Cultural space revitalisation is a specific kind of city centre renewal. It especially aims at improving a degradad urban structure in the aspect of spatial and social attractiveness. In the paper, the author deals with questions of directing a city centre revitalisation process in the right way. In author’s opinion it is needed to prove the necessity of the search for solutions to the current spatial problems within a city centre simultaneously considering some extra questions. Having reached the proper level of social and economic stabilization, other kinds of problems will be addressed subsequently. Therefore, it is necessary to think about the future right now, and programme long-term and interdisciplinary strategies for the city downtown development. In conlusion, it is essential to provide the right spatial politics to stimulate the realization of a compact city idea.